Titration method of zirconium oxide ceramic microspheres and their preparation process

Zirconia ceramic microbeads were prepared by titration method, and the cross-linking reaction of pectin and potassium aluminum sulfate and other materials was solved in the existing technology's internal structural defects and insufficient wear resistance, and achieved mass production of microbeads with uniform internal structure and good wear resistance.

CN119462138BActive Publication Date: 2025-04-22ZHEJIANG JINKUN XILI ZIRCONIUM BEAD CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510054005.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-22
Estimated Expiration
2045-01-14

AI Technical Summary

Technical Problem

The existing zirconia ceramic microbead molding method is not suitable for mass production, and there are many internal structural defects, which cannot guarantee uniformity and wear resistance.

Method used

Zirconia ceramic microbeads are prepared by titration method. By mixing yttrium stable zirconia with materials such as pectin and potassium aluminum sulfate, the microbeads with uniform internal structure and good wear resistance are formed through grinding, stirring, curing, washing, drying and sintering.

Benefits of technology

Massive production of large-particle and small-particle ceramic microbeads is achieved, ensuring the internal structural uniformity and wear resistance of the microbeads, and improving the overall performance and service life of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462138B_ABST
    Figure CN119462138B_ABST
Patent Text Reader

Abstract

The present invention discloses a titration method zirconia ceramic microbead and a preparation process thereof, and mainly relates to the technical field of ceramic compositions based on zirconia. In the prior art, the preparation process of zirconia ceramic microbeads mainly includes plastic extrusion molding, isostatic pressing molding and rolling molding. The traditional method is not completely suitable for the mass production of zirconia ceramic microbeads with different particle sizes. The prepared microbeads have many internal structural defects, the structural uniformity cannot be guaranteed, and the arrangement and bonding mode of the particles cannot be effectively controlled, resulting in uneven internal structure of the microbeads and defects. Compared with the prior art, the present invention provides a titration method zirconia ceramic microbead preparation process that can be applied to the mass production of large-particle-size and small-particle-size ceramic microbeads. Pectin is used as a binder and potassium aluminum sulfate is used as a curing agent. The two generate gel through a cross-linking reaction to wrap the zirconia particles therein, and solidify to form zirconia gel balls, and finally obtain zirconia ceramic microbeads with uniform internal structure and good wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic compositions using zirconium oxide as a base material, in particular to a titration method zirconium oxide ceramic microbead and a preparation method thereof. Background Art

[0002] At present, the production and molding technologies of spherical ceramic grinding balls at home and abroad mainly include plastic extrusion molding, isostatic pressing molding and rolling molding. The plastic extrusion molding process uses a vacuum clay machine or a hydraulic extruder to extrude mud strips, cuts the ball stones into different mud segments according to different specifications, and then uses manual or mechanical kneading to form a ball shape, and then dries to obtain a ball blank. Isostatic pressing technology overcomes traditional molding defects such as hollowness, interlayer, and lack of density, and greatly improves the performance of the product. It has high production efficiency for the production of large-particle grinding balls, but low production efficiency for the production of small-particle grinding balls. The rolling molding method is a semi-dry and wet molding method based on the production process of Chinese patent medicine pills or formed glutinous rice balls. It is formed by spraying glue to wet the ball core, sticking the wetted ball core to the outside with the added dry powder, and rolling to compact. With the help of the mutual collision, extrusion and rolling between the ball blanks or between the ball blanks and the inner wall of the ball forming machine, a dense, uniform and well-spherical ball blank is obtained. In summary, the plastic extrusion molding process is simple to operate, has high production efficiency and low equipment investment, but its fatal flaw is the low performance of the molded products; the isostatic pressing process has low requirements on the performance of raw materials, a wide range of applications, and excellent product performance. It is suitable for molding large-particle-size ceramic balls and is the development direction of large-particle-size ceramic ball molding technology; the roll forming equipment is simple, requires low investment, and has high efficiency. Although it has high requirements on the performance of raw materials and has certain difficulties in operation, it can achieve mass production with high production efficiency.

[0003] As the market's requirements for the fineness of grinding materials increase, the demand for zirconia grinding microbeads continues to increase. The existing molding methods of zirconia ceramic balls are not suitable for mass molding of zirconia ceramic microbeads. Extrusion molding and isostatic pressing are not suitable for preparing microbeads. The microbeads prepared by rolling molding have many internal structural defects and their performance cannot be guaranteed. Therefore, there is an urgent need for a new method for preparing zirconia microbeads that can improve production efficiency while meeting the market's increasing demand for the fineness of grinding materials, while ensuring that the zirconia ceramic microbeads have a uniform internal structure and excellent wear resistance.

[0004] CN118026673A discloses a method for preparing extrusion-molded zirconium oxide microbeads, which uses yttria-stabilized zirconium oxide nanopowder YSZ as raw material, and then adds a certain proportion of mixed glue and mixes evenly using an internal mixer, wherein the mixed glue is a mixture of one or more of PVA, paraffin, oleic acid, CMC and deionized water; uses an extruder to make cylindrical strips of the material and cuts them into cylindrical particles; then uses a spheronizer to roll the cylinder into a sphere with good sphericity; and then uses a high-temperature grate to burn the glue; the fired zirconium balls are polished in a polishing slurry using a grinding device, and the residual polishing liquid is rinsed with water and then dried to obtain zirconium oxide microbeads. The invention discloses a process for molding zirconium oxide microbeads using an extruder in combination with a spheronizer. The density of the prepared zirconium oxide microbeads can reach more than 99.2% of the theoretical density, with good sphericity and high crushing strength. The biggest advantage is that the molding efficiency is higher than that of the traditional rolling ball molding process, and the size of the zirconium balls is easy to control.

[0005] CN106830927A discloses a method for preparing zirconia ceramic microbeads by drop forming, the method is as follows: (1) after zirconia ceramic powder and mixed glue are mixed evenly, they are added to the drop forming equipment, and zirconia ceramic particles are first formed by drop forming, and the formed zirconia ceramic particles are formed by air cooling, and then fall into the coolant by gravity to collect and form zirconia ceramic microbead green body; (2) the collected zirconia ceramic microbead green body is taken out from the coolant, and then placed in the degreasing liquid and heated to 40-90°C for degreasing; (3) the degreased zirconia ceramic microbead green body is kept at a temperature of 1350-1550°C for 3-6 hours, and sintered into zirconia ceramic microbead blank; (4) the zirconia ceramic microbead blank is polished to obtain zirconia ceramic microbead. By adopting the method of the present invention, small-sized zirconia ceramic microbeads can be obtained, and the prepared zirconia ceramic microbeads are more uniform and more wear-resistant. The zirconia ceramic powder described in the invention is yttrium-stabilized zirconia powder or cerium-stabilized zirconia powder, and the mixed glue is composed of 0.1-15% (by weight) of polyvinyl alcohol, 84.9-99.5% (by weight) of paraffin and 0.1-5% (by weight) of oleic acid.

[0006] The solutions reported in the above patent documents do not simultaneously solve the internal structural uniformity and wear resistance of the micro-beads. Summary of the invention

[0007] In view of the above-mentioned defects of the prior art, the technical problem to be solved by the present invention is to prepare zirconia ceramic microbeads with uniform internal structure and good wear resistance by titration method, which is suitable for mass production of large-size and small-size ceramic microbeads.

[0008] To achieve the above object, the present invention provides a titration method zirconia ceramic microbead and a preparation process thereof.

[0009] A preparation process of zirconium oxide ceramic microbeads by titration method comprises the following steps, measured in parts by weight:

[0010] (1) Grinding: Add 50-60 parts of yttrium-stabilized zirconia to 100-110 parts of water, add 0.2-0.8 parts of dispersant, grind the slurry, and obtain the ground slurry for use;

[0011] (2) Stirring: Add 1-5 parts of binder to the ground slurry and stir at room temperature for 2 hours to obtain a mixed slurry for use;

[0012] (3) Curing: dripping the mixed slurry into 180-200 parts of a curing agent aqueous solution, and the droplets are cured to obtain a spherical zirconia green body for use;

[0013] (4) Washing: Add the spherical zirconia green body to water and wash it 2-4 times to remove impurity ions, and obtain the washed spherical zirconia green body for use;

[0014] (5) Drying: drying the washed spherical zirconia green body at 90-95° C. for 0.5-1 hour to obtain a dried spherical zirconia green body for use;

[0015] (6) Sintering: Sintering the dried spherical zirconia green body for 1-2 hours to obtain sintered zirconia microspheres;

[0016] (7) Polishing: Polishing the sintered zirconia microspheres in a polishing liquid until the surface is smooth, and then washing and sorting to obtain the zirconia ceramic microspheres.

[0017] The dispersant in step (1) is polyethylene glycol.

[0018] In the step (1), the slurry is ground until the median particle size of the slurry is 0.1-0.3 μm.

[0019] In the step (2), the adhesive is one of pectin and composite pectin. Preferably, the adhesive in the step (2) is composite pectin.

[0020] The preparation method of the composite pectin is as follows, in parts by weight:

[0021] 0.5-1 part of aluminum isopropoxide is added to 80-120 parts of 30-40wt% ethanol aqueous solution and stirred at 80-90°C for 1-2 hours, 10-20wt% nitric acid aqueous solution is added to adjust the pH to 3-4, stirring is continued at 85-95°C for 12 hours to age to obtain a sol, 1-5 parts of pectin are added and stirring is continued for 0.5-1 hour, and the solution is concentrated to a water content of 30-50wt% to obtain a composite pectin.

[0022] The curing agent aqueous solution in step (3) is an 8-12 wt % potassium aluminum sulfate aqueous solution.

[0023] The moisture content of the spherical zirconia green body after drying in step (5) is 1-5wt%.

[0024] The sintering temperature in step (6) is 1300-1400°C.

[0025] The polishing liquid in step (7) is nano-alumina polishing liquid.

[0026] The particle size of the zirconium oxide ceramic microbeads in step (7) is 0.03-3.2 mm.

[0027] In the prior art, the preparation process of zirconia ceramic microbeads mainly includes plastic extrusion molding, isostatic pressing molding and rolling molding. The traditional method is not completely suitable for the mass production of zirconia ceramic microbeads of different particle sizes. At the same time, the raw material performance requirements are high and the operation is difficult. The prepared microbeads have many internal structural defects, the structural uniformity is not guaranteed, and the arrangement and bonding mode of the particles cannot be effectively controlled, resulting in uneven internal structure and defects of the microbeads. The titration method of zirconia ceramic microbeads and the preparation process thereof of the present invention, firstly, yttrium-stabilized zirconia is added to water for dispersion and grinding to obtain a slurry with a median particle size between 0.1-0.3 μm, and a binder is added to make the slurry mix more uniformly and enhance the bonding force between the particles in the stirring step, and the slurry is titrated into an aqueous solution of potassium aluminum sulfate curing agent to solidify the slurry into a spherical zirconia green body, ensuring the sphericity of the microbeads. Compared with the conventional curing method, the aqueous solution of potassium aluminum sulfate curing agent provides a mild and effective curing environment, and the particles are quickly formed into a stable connection and solidified into a ball without destroying the structure of the zirconia particles and other additives. Finally, after washing, drying and sintering, impurity ions are removed, the moisture content is controlled and sintered at a specific temperature to obtain zirconia ceramic microbeads with uniform internal structure and good wear resistance; finally, the surface of the microspheres is smoothed by a polishing step, thereby improving the product quality. The method of the present invention is applicable to the mass production of large-size and small-size ceramic microbeads, and provides an efficient and reliable method for the preparation of zirconia ceramic microbeads.

[0028] The present invention uses pectin as a binder. Pectin has excellent viscosity and can firmly bond the zirconium oxide particles during the stirring process, which not only ensures the bonding stability of the slurry in each preparation step, but also makes the bonding between the particles more firm and less likely to loosen during the subsequent curing, drying and sintering processes, thereby laying the foundation for forming a uniform internal structure. Conventional binders often find it difficult to take both viscosity and dispersibility into account at the same time, and easily cause the zirconium oxide particles to aggregate and precipitate in the slurry, thereby affecting the quality of the microbeads. Pectin can improve the dispersibility of the slurry while ensuring good viscosity, so that the yttrium-stabilized zirconium oxide particles are evenly distributed in the water. In the subsequent processing process, the evenly dispersed particles can be better cured and sintered, further promoting the uniformity of the internal structure of the microbeads.

[0029] Pectin is used as a binder and potassium aluminum sulfate is used as a curing agent. The two react through cross-linking to generate gel that wraps the zirconium oxide particles, and solidify to form zirconium oxide gel balls. Bonding and solidification occur simultaneously, and pectin and potassium aluminum sulfate are indispensable. By regulating the solidification behavior of zirconium oxide particles, the process of solidifying the slurry into a spherical zirconium oxide green body is made more uniform and stable, which promotes the fusion and crystallization between particles and forms a highly uniform internal structure, allowing the microbeads to withstand greater pressure and friction during use, thereby improving the overall performance and service life of the microbeads. Finally, pectin enhances the bonding force between zirconium oxide particles, making it difficult for zirconium oxide ceramic microbeads to fall off and be damaged when subjected to friction and impact. At the same time, the uniform internal structure also reduces the stress concentration points inside the microbeads, reducing the risk of overall failure of the microbeads due to local wear during use. In contrast, conventional adhesives cannot provide such excellent wear resistance guarantees.

[0030] Furthermore, the present invention performs compound modification on the pectin adhesive, firstly using aluminum isopropoxide as a precursor to prepare boehmite sol, which has good crystallinity. When used in combination with the pectin adhesive, its good crystallinity can make the structure of the composite system more regular and orderly, thereby promoting the uniform dispersion of yttrium-stabilized zirconia particles, avoiding particle agglomeration, and thus helping to form a uniform internal structure. In the subsequent curing and sintering process, the composite pectin continues to play a role, further enhancing the bonding force between particles, reducing the generation of internal defects, so that when the zirconia ceramic microbeads are subjected to external forces, their internal structure can evenly withstand pressure and friction, and can better resist wear, thereby improving the overall wear resistance.

[0031] Beneficial effects of the present invention:

[0032] Compared with the prior art, the preparation process of zirconia ceramic microbeads in the prior art mainly includes plastic extrusion molding, isostatic pressing molding and rolling molding. The traditional method is not completely suitable for the mass production of zirconia ceramic microbeads of different particle sizes. At the same time, the raw material performance requirements are high and the operation is difficult. The prepared microbeads have many internal structural defects, the structural uniformity cannot be guaranteed, and the arrangement and bonding mode of the particles cannot be effectively controlled, resulting in uneven internal structure and defects of the microbeads. The present invention provides a titration method for preparing zirconia ceramic microbeads, which can be applied to the mass production of large-particle-size and small-particle-size ceramic microbeads. Pectin is used as a binder and potassium aluminum sulfate is used as a curing agent. The two generate gel through a cross-linking reaction to wrap the zirconia particles therein, and solidify to form zirconia gel balls. Bonding and curing occur simultaneously. Pectin and potassium aluminum sulfate are indispensable, and finally zirconia ceramic microbeads with uniform internal structure and good wear resistance are obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1This is the test report of zirconia ceramic microbeads in Example 1.

[0034] Figure 2 This is the process flow chart of zirconia ceramic microbeads.

[0035] Figure 3 Schematic diagram of the microstructure of zirconia ceramic microbeads prepared by the titration method in Example 1.

[0036] Figure 4 This is a schematic diagram of the surface structure of zirconia ceramic microbeads obtained by the titration method in Example 1.

[0037] Figure 5 This is a schematic diagram of the internal structure of zirconia ceramic microbeads in the titration method of Example 1. DETAILED DESCRIPTION

[0038] The parameters of the specific chemical substances used in the examples are from the following sources:

[0039] Yttrium stabilized zirconia: powder, particle size 30-40nm, density 5.5g / cm 3 , Y2O3 content 3mol%.

[0040] Pectin: The manufacturer is Nanjing Dulai Biotechnology Co., Ltd., and the product number is C0077.

[0041] Nano-alumina polishing liquid: solid content ≥30%, particle size 100nm, manufacturer is Changzhou Konada New Material Technology Co., Ltd., model is KND-LP30.

[0042] Example 1

[0043] A preparation process of zirconium oxide ceramic microbeads by titration method comprises the following steps:

[0044] (1) Grinding: Add 500 g of yttrium-stabilized zirconia to 1000 g of water, add 5 g of polyethylene glycol (PEG-2000), grind the slurry, and the median particle size is 0.2 μm to obtain the ground slurry for use;

[0045] (2) Stirring: Add 30 g of pectin to the ground slurry and stir at room temperature for 2 hours to obtain a mixed slurry for later use;

[0046] (3) Solidification: The mixed slurry is dropped into 1900 g of a 10 wt% potassium aluminum sulfate aqueous solution, and the droplets are solidified to obtain a spherical zirconia green body for use;

[0047] (4) Washing: Add the spherical zirconia green body to water and wash it three times to remove impurity ions, and obtain the washed spherical zirconia green body for use;

[0048] (5) Drying: The washed spherical zirconia green body is placed at 90° C. and dried for 1 hour, and the moisture content is 2.5 wt %. The dried spherical zirconia green body is obtained for later use;

[0049] (6) Sintering: The dried spherical zirconia green body is sintered at 1350° C. for 1.5 hours to obtain sintered zirconia microspheres.

[0050] (7) Polishing: The sintered zirconia microspheres are polished in a nano-alumina polishing liquid until the surface is smooth, and then cleaned and sorted to obtain the zirconia ceramic microspheres with a particle size of 0.6-0.7 mm.

[0051] Example 2

[0052] A preparation process of zirconium oxide ceramic microbeads by titration method comprises the following steps:

[0053] (1) Grinding: Add 500 g of yttrium-stabilized zirconia to 1000 g of water, add 5 g of polyethylene glycol (PEG-2000), grind the slurry, and the median particle size is 0.2 μm to obtain the ground slurry for use;

[0054] (2) Stirring: Add 30 g of composite pectin to the ground slurry and stir at room temperature for 2 hours to obtain a mixed slurry for later use;

[0055] (3) Solidification: The mixed slurry is dropped into 1900 g of a 10 wt% potassium aluminum sulfate aqueous solution, and the droplets are solidified to obtain a spherical zirconia green body for use;

[0056] (4) Washing: Add the spherical zirconia green body to water and wash it three times to remove impurity ions, and obtain the washed spherical zirconia green body for use;

[0057] (5) Drying: The washed spherical zirconia green body is placed at 90° C. and dried for 1 hour, and the moisture content is 2.5 wt %. The dried spherical zirconia green body is obtained for later use;

[0058] (6) Sintering: The dried spherical zirconia green body is sintered at 1350° C. for 1.5 hours to obtain sintered zirconia microspheres.

[0059] (7) Polishing: The sintered zirconia microspheres are polished in a nano-alumina polishing liquid until the surface is smooth, and then cleaned and sorted to obtain the zirconia ceramic microspheres with a particle size of 0.6-0.7 mm.

[0060] The preparation method of the composite pectin is as follows:

[0061] Add 10 g of aluminum isopropoxide to 1000 g of 35 wt % ethanol aqueous solution and stir at 85 ° C for 1.5 hours, add 10 wt % nitric acid aqueous solution to adjust the pH to 3.8, continue stirring at 90 ° C for 12 hours to age to obtain a sol, add 30 g of pectin and continue stirring for 0.5 hours, and concentrate to a water content of 40 wt % to obtain a composite pectin.

[0062] Comparative Example 1

[0063] A preparation process of zirconium oxide ceramic microbeads by titration method comprises the following steps:

[0064] (1) Grinding: Add 500 g of yttrium-stabilized zirconia to 1000 g of water, add 5 g of polyethylene glycol (PEG-2000), grind the slurry, and the median particle size is 0.2 μm to obtain the ground slurry for use;

[0065] (2) Stirring: Add 30 g of sodium alginate to the ground slurry and stir at room temperature for 2 hours to obtain a mixed slurry for later use;

[0066] (3) Solidification: The mixed slurry is dropped into 1900 g of a 10 wt% potassium aluminum sulfate aqueous solution, and the droplets are solidified to obtain a spherical zirconia green body for use;

[0067] (4) Washing: Add the spherical zirconia green body to water and wash it three times to remove impurity ions, and obtain the washed spherical zirconia green body for use;

[0068] (5) Drying: The washed spherical zirconia green body is placed at 90° C. and dried for 1 hour, and the moisture content is 2.5 wt %. The dried spherical zirconia green body is obtained for later use;

[0069] (6) Sintering: The dried spherical zirconia green body is sintered at 1350° C. for 1.5 hours to obtain sintered zirconia microspheres.

[0070] (7) Polishing: The sintered zirconia microspheres are polished in a nano-alumina polishing liquid until the surface is smooth, and then cleaned and sorted to obtain the zirconia ceramic microspheres with a particle size of 0.6-0.7 mm.

[0071] Comparative Example 2

[0072] A preparation process of zirconium oxide ceramic microbeads by titration method comprises the following steps:

[0073] (1) Grinding: Add 500 g of yttrium-stabilized zirconia to 1000 g of water, add 5 g of polyethylene glycol (PEG-2000), grind the slurry, and the median particle size is 0.2 μm to obtain the ground slurry for use;

[0074] (2) Stirring: Add 30 g of gelatin to the ground slurry and stir at room temperature for 2 hours to obtain a mixed slurry for later use;

[0075] (3) Solidification: The mixed slurry is dropped into 1900 g of a 10 wt% potassium aluminum sulfate aqueous solution, and the droplets are solidified to obtain a spherical zirconia green body for use;

[0076] (4) Washing: Add the spherical zirconia green body to water and wash it three times to remove impurity ions, and obtain the washed spherical zirconia green body for use;

[0077] (5) Drying: The washed spherical zirconia green body is placed at 90° C. and dried for 1 hour, and the moisture content is 2.5 wt %. The dried spherical zirconia green body is obtained for later use;

[0078] (6) Sintering: The dried spherical zirconia green body is sintered at 1350° C. for 1.5 hours to obtain sintered zirconia microspheres.

[0079] (7) Polishing: The sintered zirconia microspheres are polished in a nano-alumina polishing liquid until the surface is smooth, and then cleaned and sorted to obtain the zirconia ceramic microspheres with a particle size of 0.6-0.7 mm.

[0080] Comparative Example 3

[0081] A preparation process of zirconium oxide ceramic microbeads by titration method comprises the following steps:

[0082] (1) Grinding: Add 500 g of yttrium-stabilized zirconia to 1000 g of water, add 5 g of polyethylene glycol (PEG-2000), grind the slurry, and the median particle size is 0.2 μm to obtain the ground slurry for use;

[0083] (2) Stirring: Add 30 g of composite pectin to the ground slurry and stir at room temperature for 2 hours to obtain a mixed slurry for later use;

[0084] (3) Solidification: The mixed slurry is dropped into 1900 g of a 10 wt% zinc sulfate aqueous solution, and the droplets are solidified to obtain a spherical zirconia green body for use;

[0085] (4) Washing: Add the spherical zirconia green body to water and wash it three times to remove impurity ions, and obtain the washed spherical zirconia green body for use;

[0086] (5) Drying: The washed spherical zirconia green body is placed at 90° C. and dried for 1 hour, and the moisture content is 2.5 wt %. The dried spherical zirconia green body is obtained for later use;

[0087] (6) Sintering: The dried spherical zirconia green body is sintered at 1350° C. for 1.5 hours to obtain sintered zirconia microspheres.

[0088] (7) Polishing: The sintered zirconia microspheres are polished in a nano-alumina polishing liquid until the surface is smooth, and then cleaned and sorted to obtain the zirconia ceramic microspheres with a particle size of 0.6-0.7 mm.

[0089] The preparation method of the composite pectin is as follows:

[0090] Add 10 g of aluminum isopropoxide to 1000 g of 35 wt % ethanol aqueous solution and stir at 85 ° C for 1.5 hours, add 10 wt % nitric acid aqueous solution to adjust the pH to 3.8, continue stirring at 90 ° C for 12 hours to age to obtain a sol, add 30 g of pectin and continue stirring for 0.5 hours, and concentrate to a water content of 40 wt % to obtain a composite pectin.

[0091] Comparative Example 4

[0092] A preparation process of zirconium oxide ceramic microbeads by titration method comprises the following steps:

[0093] (1) Grinding: Add 500 g of yttrium-stabilized zirconia to 1000 g of water, add 5 g of polyethylene glycol (PEG-2000), grind the slurry, and the median particle size is 0.2 μm to obtain the ground slurry for use;

[0094] (2) Stirring: Add 30 g of composite pectin to the ground slurry and stir at room temperature for 2 hours to obtain a mixed slurry for later use;

[0095] (3) Solidification: The mixed slurry is dropped into 1900 g of a 10 wt% aluminum chloride aqueous solution, and the droplets are solidified to obtain a spherical zirconia green body for use;

[0096] (4) Washing: Add the spherical zirconia green body to water and wash it three times to remove impurity ions, and obtain the washed spherical zirconia green body for use;

[0097] (5) Drying: The washed spherical zirconia green body is placed at 90° C. and dried for 1 hour, and the moisture content is 2.5 wt %. The dried spherical zirconia green body is obtained for later use;

[0098] (6) Sintering: The dried spherical zirconia green body is sintered at 1350° C. for 1.5 hours to obtain sintered zirconia microspheres.

[0099] (7) Polishing: The sintered zirconia microspheres are polished in a nano-alumina polishing liquid until the surface is smooth, and then cleaned and sorted to obtain the zirconia ceramic microspheres with a particle size of 0.6-0.7 mm.

[0100] The preparation method of the composite pectin is as follows:

[0101] Add 10 g of aluminum isopropoxide to 1000 g of 35 wt % ethanol aqueous solution and stir at 85 ° C for 1.5 hours, add 10 wt % nitric acid aqueous solution to adjust the pH to 3.8, continue stirring at 90 ° C for 12 hours to age to obtain a sol, add 30 g of pectin and continue stirring for 0.5 hours, and concentrate to a water content of 40 wt % to obtain a composite pectin.

[0102] Test Example 1

[0103] The zirconia ceramic microbeads prepared by the preparation methods of Examples 1-2 and Comparative Examples 1-4 were subjected to a self-wear rate test. 300 g of zirconia ceramic microbeads were randomly divided into three groups for parallel tests, and the test data were averaged. The test was based on the industry standard JC / T 2136-2012 "Microcrystalline Zirconia Grinding Media Balls", as summarized in Table 1.

[0104] Table 1 Self-wear rate test data

[0105]

[0106] The difference between the embodiment and the comparative example in Test Example 1 lies in the difference in the adhesive and the curing agent. The pectin used in Example 1 as an adhesive has good viscosity and can firmly bond the zirconium oxide particles during stirring, ensuring close bonding between the particles in subsequent processes. Its dispersibility helps to evenly distribute the particles, promotes solidification and sintering to form a uniform internal structure, and enhances the overall performance of the microbeads, thereby reducing the self-wear rate to 0.010%, which is lower than that of Comparative Examples 1-2. The composite pectin in Example 2 is based on pectin and added with boehmite sol prepared with aluminum isopropoxide as a precursor to further optimize the performance, reducing the self-wear rate to 0.008%. In Comparative Examples 1-2, sodium alginate and gelatin are used as adhesives respectively. The viscosity of sodium alginate and its binding force with zirconium oxide particles are low. During the processing, the stable binding between particles cannot be effectively maintained, resulting in an increase in internal structural defects. In the wear test, the surface and internal particles of the microbeads are more likely to fall off, which increases the self-wear rate. Although the gelatin used in Comparative Example 2 has a certain degree of adhesion, compared with pectin and its composite products, it is not as effective in ensuring uniform dispersion of particles, tight binding and promoting structural uniformity. The internal structure uniformity and the bonding strength between particles are not as good as those in the embodiment, and the self-wear rate increases. Comparative Examples 3-4 respectively replace the potassium aluminum sulfate aqueous solution curing agent with zinc sulfate and aluminum chloride on the basis of Example 2, and the self-wear rate is improved. Therefore, both the adhesive and the curing agent will affect the molding stabilizer of the ceramic microbeads and thus affect the self-wear rate.

[0107] Test Example 2

[0108] The surface roughness of the zirconia ceramic microbeads prepared by the preparation methods of Examples 1-2 and Comparative Examples 1-4 was tested. 300 g of zirconia ceramic microbeads were randomly divided into three groups for parallel tests, and the test data were averaged. The test was based on the industry standard JC / T 2136-2012 "Microcrystalline Zirconia Grinding Media Balls", as summarized in Table 2.

[0109] Table 2 Surface roughness test data

[0110]

[0111] The difference between the embodiment and the comparative example in Test Example 2 lies in the difference in the adhesive and the curing agent. In Example 1, pectin is used as a binder. Its good viscosity and dispersibility help to evenly disperse the zirconium oxide particles and tightly combine them in each preparation step, and it is conducive to forming a uniform structure in the subsequent curing, sintering and other processes, and the surface roughness is low. Example 2 uses composite pectin as a binder. The sol formed by aluminum isopropoxide is compounded with pectin during its preparation process, which further optimizes the performance, makes the microbead structure more uniform, the surface smoother, and the surface roughness is as low as 0.006μm. Comparative Example 1 uses sodium alginate as a binder, which cannot effectively maintain the uniform distribution and tight combination of particles in combination with a curing agent, resulting in many internal structural defects; the gelatin bonding stability of Comparative Example 2 is lower than that of the binder in the embodiment, making the surface of the microbead not smooth enough; Comparative Examples 3-4 use zinc sulfate and aluminum chloride as curing agents, respectively, which are different from the potassium aluminum sulfate aqueous solution curing agent in the embodiment, and the structural uniformity is slightly poor. Therefore, the surface roughness of Comparative Examples 1-4 is lower than that of Examples 1-2.

[0112] Test Example 3

[0113] The zirconia ceramic microbeads prepared by the method of Example 1 were sent for inspection. The inspection report is as follows: Figure 1 shown.

[0114] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.

Claims

1. A preparation process of zirconium oxide ceramic microspheres by titration, characterized in that: The method comprises the following steps, in parts by weight: (1) Grinding: adding 50-60 parts of yttrium-stabilized zirconia to 100-110 parts of water, adding 0.2-0.8 parts of dispersant, grinding the slurry to obtain a ground slurry for use; (2) stirring: add 1-5 parts of a binder to the ground slurry, stir at room temperature for 2 hours to obtain a mixed slurry for later use; (3) Curing: dripping the mixed slurry into 180-200 parts of a curing agent aqueous solution, and the droplets are cured to obtain a spherical zirconia green body for use; (4) Washing: adding the spherical zirconia green body to water and washing it 2-4 times to remove impurity ions, and obtaining the washed spherical zirconia green body for use; (5) Drying: drying the washed spherical zirconia green body at 90-95° C. for 0.5-1 hour to obtain a dried spherical zirconia green body for later use; (6) Sintering: Sintering the dried spherical zirconia green body for 1-2 hours to obtain sintered zirconia microspheres; (7) polishing: polishing the sintered zirconia microspheres in a polishing liquid until the surface is smooth, and washing and sorting to obtain the zirconia ceramic microspheres; In the step (2), the adhesive is composite pectin; The preparation method of the composite pectin is as follows, in parts by weight: 0.5-1 part of aluminum isopropoxide is added to 80-120 parts of 30-40 wt% ethanol aqueous solution, stirred at 80-90° C. for 1-2 hours, 10-20 wt% nitric acid aqueous solution is added to adjust the pH to 3-4, and the mixture is stirred at 85-95° C. for 12 hours to obtain a sol, 1-5 parts of pectin are added, and the mixture is stirred for 0.5-1 hour, and the mixture is concentrated to a water content of 30-50 wt% to obtain a composite pectin; The curing agent aqueous solution in step (3) is an 8-12 wt % potassium aluminum sulfate aqueous solution.

2. The preparation process of zirconium oxide ceramic microspheres by titration method according to claim 1, characterized in that: The dispersant in step (1) is polyethylene glycol.

3. The preparation process of zirconium oxide ceramic microspheres by titration method according to claim 1, characterized in that: In the step (1), the slurry is ground until the median particle size of the slurry is 0.1-0.3 μm.

4. The preparation process of zirconium oxide ceramic microspheres by titration method according to claim 1, characterized in that: The sintering temperature in step (6) is 1300-1400°C.

5. The preparation process of zirconium oxide ceramic microspheres by titration method according to claim 1, characterized in that: The polishing liquid in step (7) is nano-alumina polishing liquid.

6. The preparation process of zirconium oxide ceramic microbeads by titration method according to claim 1, characterized in that: The particle size of the zirconia ceramic microbeads in step (7) is 0.03-3.2 mm.

7. A titration method of zirconium oxide ceramic microbeads, characterized in that: The invention is prepared by the preparation process according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Preparation method of extrusion-molded zirconia microspheres

    CN118026673A

  • Method for preparing zirconium oxide ceramic micro-beads through titration forming

    CN106830927A

  • Method for preparing zirconia ceramic microspheres

    CN110835263A